Why Australians Will Never Be Prosperous - Barbato, C; Hamilton, C (My University, 2005)
Research by The Australia Institute has revealed that, despite being well off by any objective standards, most Australians believe that their incomes are inadequate to meet their needs. A Newspoll survey for the Institute found that 62 per cent of Australians, including 48 per cent of the richest 20 per cent, believe that they cannot afford to buy everything they really need.
Australia Institute Webpaper
Keywords: Finance -- Wealth; Finance; Income, wealth and finances; Income, wealth and finances